Performance Art Center - دانا كنعان (My University, 2025)
The design of a performance art center embodies the intersection of architecture, engineering, and artistic expression creating a dynamic space that fosters cultural enrichment and community engagement. this project explores the integration of cutting-edge acoustics, flexible spatial planning, and sustainable building technologies to craft a venue capable of hosting diverse performances from theatrical productions to live concerts and multimedia art installations. The architectural design prioritizes adaptability with modular seating arrangements and multipurpose halls that can transform to accommodate varying audience sizes and performance chambers ensure unparalleled sound quality throughout the center. Environmental considerations drive the projects core with energy-efficient lighting, HVAC system, and sustainable materials reducing the buildings carbon footprint while enhancing user comfort. Fire safety and emergency evacuation strategies are incorporated in compliance with international standards providing a secure environment without compromising the aesthetic and functional innovation serving as both a canvas for artistic creativity and model for forward-thinking architectural design. This performance arts center aspires to serve as a cultural landmark and a hub for creativity, education, and innovation. It aims to redefine the relationship between architecture and performance setting a benchmark for sustainable and technologically advanced cultural spaces that inspire and engage diverse communities.